Gravity and Magnetic Modeling of Central Italy: Insights Into the Depth Extent of the Seismogenic Layer. (30th April 2019) - Mancinelli, P.; Porreca, M.; Pauselli, C.; Minelli, G.; Barchi, M.R.; Speranza, F.
Abstract: The recent 2016–2017 seismic sequence in Central Italy has prompted the investigation of several geological and geophysical data in order to derive more accurate subsurface geological models. We present the results of combined gravity and magnetic modeling performed along three sections crossing the area of the seismic sequence in order to evaluate the geological parameters controlling or affecting the thickness of the seismogenic layer of this part of the Apennines. The models are constructed using all the available geological and petrophysical constraints derived from previous studies. Resulting models are consistent with the top of the basement located at 8‐ to 12‐km depth and contribute to the geological and geophysical understanding of the area investigating the role of the basement in the seismic events. The basement, involved in Miocene thrusting, formed the base of seismicity for the recent seismic sequence in the area. Moreover, the models provide information about the nature and composition of the basement and lower crust. Finally, these findings contribute in the investigation of the mechanisms controlling the thickness of the seismogenic layer in extensional postorogenic scenarios. Plain Language Summary: In geologically complex regions such as the Apennines (Italy), surface observations and deeper information should be combined in a multidisciplinary approach to advance understanding of the factors that influence the distribution of earthquakes. The geologic and geophysical models are combined here to investigate the thickness of the crustal bodies capable of generating seismic events such those observed during the 2016–2017 seismic sequence. Results coherently show that seismic events are mostly located in the sedimentary units, and this will help in the general understanding of how the Apennines and similar chains evolve. Key Points: Combined gravity and magnetic anomaly models are produced for the active seismic sector of Central Italy Models are constrained with surface geology and recent geological models The models provide information regarding the depth distribution of the basement and highlight its role in controlling the seismicity cutoff